2005
DOI: 10.1089/neu.2005.22.1319
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Scales in Traumatic Brain Injury: A Comparison of the Glasgow Outcome Scale (Extended) and the Functional Status Examination

Abstract: Clinical trials aimed at developing therapies for traumatic brain injury (TBI) require outcome measures that are reliable, validated, and easily administered. The most widely used of these measures, the Glasgow Outcome Scale (GOS) and the GOS-Extended (GOS-E), have been criticized as suffering from ceiling effects. In an attempt to develop a more useful and dynamic outcome measure, the Functional Status Examination (FSE) was developed, which grades outcome across 10 functional domains. The FSE has been demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 17 publications
2
46
0
1
Order By: Relevance
“…Dikmen et al (2001Dikmen et al ( , 2003 demonstrated that FSE is more sensitive to recovery at 1-6 months compared to GOS. Our previous study also showed that FSE and GOS-E scores correlated well with each other (r ¼ À0.83), while FSE is a more sensitive outcome measurement (Hudak et al, 2005).…”
Section: Functional Outcome Measurementioning
confidence: 54%
“…Dikmen et al (2001Dikmen et al ( , 2003 demonstrated that FSE is more sensitive to recovery at 1-6 months compared to GOS. Our previous study also showed that FSE and GOS-E scores correlated well with each other (r ¼ À0.83), while FSE is a more sensitive outcome measurement (Hudak et al, 2005).…”
Section: Functional Outcome Measurementioning
confidence: 54%
“…Elevated D-dimer level has also been shown to relate to early clinical progression [5], stroke subtypes [6], and infarction volume [7]. Some studies have suggested that D-dimer can be seen as an outcome predictor in ischemic stroke and an indicator of severity of traumatic brain injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study has some important limitations: first, it is a retrospective analysis and is therefore subject to the limitations of such analyses. Due to its retrospective design, a weakness of our study is a deficiency in accurately collecting some history and clinical information like formal neurologic or functional severity scores [29][30][31][32] and the number of the patients who receiving mild-induced hypothermia, which has been demonstrated to have a strong beneficial impact on long-term survival and neurological status in the setting of outof-hospital cardiac arrest [33]. Secondly, the nonrandomized nature of the comparison may have resulted into bias: for this reason, propensity score matching further enhanced the comparability of the patients.…”
Section: Discussionmentioning
confidence: 99%